Ventricular function in noncardiacs with alcoholic fatty liver: role of ethanol in the production of cardiomyopathy - Regan, Timothy J. (1969)
Since many patients with cardiomyopathy have a history of chronic ethanolism often associated with malnutrition, we have evaluated left ventricular (LV) function in alcoholics with fatty liver, who had no clinical evidence of cardiac or nutritional disease. During an afterload test of LV function the pressor response to angiotensin evoked a threefold rise of enddiastolic pressure in the alcoholic group which was substantially greater than the 4 mm Hg rise in control subjects. The stroke volume and stroke work response in the noncardiac alcoholic was significantly less than in controls. Diminished LV function was corroborated in the noncardiac alcoholic at rest, using a contractility index. To evaluate the dose-response relationship of ethanol in the production of cardiac malfunction, two groups of noncardiac alcoholic subjects were studied acutely at low and moderate dose levels. After 6 oz, ventricular function, myocardial blood flow, and metabolism were not significantly affected. After 12 oz, there was a progressive rise of end-diastolic pressure and decrease of stroke output at a mean blood alcohol level of 150 mg/100 ml, reverting toward control by 4 hr. The coronary effluent transiently evidenced leakage of cell constituents, despite an increase of coronary blood flow, suggesting a direct but reversible cardiac injury. Myocardial extraction of triglyceride was enhanced, whereas FFA uptake was reduced. A possible role of myocardial triglyceride accumulation in heart muscle was considered in pathogenesis. Chronic ingestion of 16 oz of Scotch daily by an alcoholic subject while on a normal diet produced, after 12 wk, a progressive increase of heart rate and size, circulation time, and venous pressure, and a ventricular diastolic gallop. Normal values were restored within 7 wk after interrupting alcohol. These several studies suggest that the cumulative effects of repeated ingestion of ethanol in intoxicating doses can produce diminished LV function before clinical evidence of cardiac abnormality, or heart disease not necessarily related to malnutrition.